Analisis Kerentanan Hunian Perkotaan terhadap Urban Heat Berbasis Sistem Penghawaan dan Pencahayaan - Jelita Bulanisahadi; Agil Fitri Handayani; Nazwa Laily Azzahrah; Laura Angelica Fadia Indriani; Tee Tze Kiong (Program Studi Arsitektur Universitas Tanri Abeng, 2026)
This study analyzes the vulnerability of two-story residential buildings to increasing urban temperatures caused by the urban heat island phenomenon. A descriptive quantitative approach was used through field observations on houses with different ventilation and opening characteristics. The data collected include indoor air temperature, relative humidity, and natural lighting intensity. The results show that houses with cross ventilation and larger opening ratios have lower indoor temperatures and better natural lighting performance. These findings indicate that passive design strategies play an important role in improving thermal comfort and reducing the impact of urban heat in residential buildings.